2013
DOI: 10.1111/corg.12042
|View full text |Cite
|
Sign up to set email alerts
|

CEO Characteristics and Internal Control Quality

Abstract: Manuscript Type Empirical Research Question/Issue This study investigates the influence of CEO characteristics on internal control quality in the U.S. Research Findings/Insights Using a sample of 4,374 ExecuComp non‐financial firms, we find that CEO entrenchment and age are significantly associated with a material internal control weakness disclosure (MW) under Sarbanes‐Oxley Section 404 (SOX 404). Our results demonstrate that entrenchment and age may affect CEOs' behavior in response to the SOX 404 internal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 117 publications
5
75
1
2
Order By: Relevance
“…There is also evidence that the CEO's age has a significant effect on mergers and acquisitions (Yim (2013). Lin et al (2014) found a significant negative relationship between CEOs' age and internal control quality. On the other hand, Bamber et al (2010) reported that managers born before World War II are more likely to have developed conservative communication styles than managers born after the war.…”
Section: Theoretical Framework and The Development Of A Hypothesismentioning
confidence: 99%
“…There is also evidence that the CEO's age has a significant effect on mergers and acquisitions (Yim (2013). Lin et al (2014) found a significant negative relationship between CEOs' age and internal control quality. On the other hand, Bamber et al (2010) reported that managers born before World War II are more likely to have developed conservative communication styles than managers born after the war.…”
Section: Theoretical Framework and The Development Of A Hypothesismentioning
confidence: 99%
“…To improve internal financial decisions, researchers found that high-quality internal controls improved the efficiency of investments and the ability to manage uncertainty [38]. Those companies with higher levels of internal control have lower equity capital and bank debt costs, and more commercial credit financing compared to others in the industry [39][40][41]. In summary, internal controls are not the only management activity available to improve efficiency and prevent risk, but are important for value creation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following prior studies [30][31][32]41], we used several control variables for the factors that have been shown to affect the dependent variables of stock price crash risk and internal control efficiency.…”
Section: Control Variablesmentioning
confidence: 99%
“…The study measures the CEO age as the difference between date of birth and the years of the study period (Cornett et al 2009;Lin et al 2014). …”
Section: Independent Variablesmentioning
confidence: 99%